Pengaruh kualitas pelayanan elektronik dan kepuasan terhadap kepercayaan konsumen serta dampaknya terhadap loyalitas konsumen - Siti Marwanah; Muchsin Saggaf Shihab (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of banking digitalization continues and has a significant impact on the market, plus the pandemic situation that has changed people's consumption and daily lifestyles. In addition, the use of smartphones as a daily necessity has changed the perspective of seeing the banking industry, which is a provider of financial services that collect public funds. The factors of service quality and Trust are also determinants of customer loyalty. This study aimed to determine the effect of E-Servqual and Satisfactions on Trust and their impact on Loyalty. This research is causal, and the research instrument is a questionnaire with a purposive sampling technique with 165 respondents. This research method uses path analysis with SPSS tools. The results showed a positive relationship between E-Servqual on the formation of Trust, the effect of Satisfaction on the formation of Trust, the influence of Satisfaction on the formation of Loyalty, the influence of Trust on the formation of Loyalty. Another finding is that E-Servqual does not affect the formation of Loyalty. Therefore, the Trust acts as a mediator or intermediary that can form a Loyalty if it already exists. If there is no Trust, then there will be no Loyalty, even though the quality of service is good and Satisfaction already exists in the users, but without Trust, Loyalty will not be created.